If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (N + 3)(n + 6) = 0 Reorder the terms: (3 + N)(n + 6) = 0 Reorder the terms: (3 + N)(6 + n) = 0 Multiply (3 + N) * (6 + n) (3(6 + n) + N(6 + n)) = 0 ((6 * 3 + n * 3) + N(6 + n)) = 0 ((18 + 3n) + N(6 + n)) = 0 (18 + 3n + (6 * N + n * N)) = 0 (18 + 3n + (6N + nN)) = 0 Reorder the terms: (18 + 6N + 3n + nN) = 0 (18 + 6N + 3n + nN) = 0 Solving 18 + 6N + 3n + nN = 0 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-18' to each side of the equation. 18 + 6N + 3n + -18 + nN = 0 + -18 Reorder the terms: 18 + -18 + 6N + 3n + nN = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 6N + 3n + nN = 0 + -18 6N + 3n + nN = 0 + -18 Combine like terms: 0 + -18 = -18 6N + 3n + nN = -18 Add '-3n' to each side of the equation. 6N + 3n + -3n + nN = -18 + -3n Combine like terms: 3n + -3n = 0 6N + 0 + nN = -18 + -3n 6N + nN = -18 + -3n Reorder the terms: 18 + 6N + 3n + nN = -18 + -3n + 18 + 3n Reorder the terms: 18 + 6N + 3n + nN = -18 + 18 + -3n + 3n Combine like terms: -18 + 18 = 0 18 + 6N + 3n + nN = 0 + -3n + 3n 18 + 6N + 3n + nN = -3n + 3n Combine like terms: -3n + 3n = 0 18 + 6N + 3n + nN = 0 The solution to this equation could not be determined.
| ax-bx=12 | | cx+3h=58 | | 0=16-4x^2 | | b+4=12 | | 2m^2=-8-8m | | 6y^2-13y+6=0 | | .75x+3=9 | | -12(x-4)=-3(6x+2) | | -x-3=-4x-14 | | 0.65x+.05(8-x)=.10(-8) | | 3lx-5l-2x=10 | | x-1(3x-9)=-5 | | 4y=9x+4f | | a-5=2a | | x-1(3x-9)=5x | | 4x^2-32x=-60 | | a+1-5*6=b+56 | | -3(x-1)=2(1-2x) | | -8(1+5r)=11(-4r-3)-11 | | 5x+2y+(3x-y)+(2x-y)= | | abcdefg-hijklmn=42 | | y=p^2-2p+2 | | (3x-y)+(2x-y)= | | 17x+8=42+12x-4 | | -3x+7=2-4x | | 18-3x+12=57 | | 146+2x=2x+26+172 | | -9x+x^2=-14 | | 5x-5=6x-3 | | -9x+2=-14 | | 7x=3x^2+1 | | 9x^2+11x=-5 |